Harnessing Indigenous Technologies for Sustainable Management of Land, Water, and Food Resources Amidst Climate Change - Imoro, Ziblim Abukari; Imoro, Abubakari Zarouk; Duwiejuah, Abudu Ballu; Abukari, Ammal (Frontiers in Sustainable Food Systems, 2021)
Through advancements in technology humans have cultivated more food, used more fossil fuel reserves, polluted the environment, and caused climate change. This was not the case some few decades ago where indigenous technologies were used in exploiting natural resources. Unfortunately, the effects of climate change on the planet are no more distant reality. The melting of glaciers, rising sea levels, extreme rainfall, and prolonged drought are already being experienced. These have affected water resources, land, and food security across the world. The limits of conventional climate change adaptation and mitigation strategies call for the integration of indigenous knowledge and technologies for tackling climate change issues. This is because of the importance that indigenous knowledge and technologies have for identifying the impacts and as well providing effective adaption and mitigation strategies to climate change. Thus, this chapter explores the potential of indigenous knowledge and technologies for the sustainable management of water, land, and food security amidst climate change. The applications of indigenous technologies and knowledge such as agroforestry, the use of sacred groves to conserve water, land, and biodiversity resources, and the practising of conservation-agriculture are discussed as solutions for reducing greenhouse gas emissions, water shortages, land degradation, and pollution. However, these indigenous technologies will be less useful in today's world if not harnessed. Thus also in this chapter, the scientific know-how available to improve the effectiveness of indigenous technologies for the sustainable use of water, land, and food resources have been identified (Robotics, sensors/detectors, internet of things) and discussed.